(untitled) (Contemporary Journal of Social Science Review, 2025)
The advent of advanced medical technologies has introduced gender selection as a potential intervention within infertility treatment, enabling couples to influence the sex of their offspring prior to conception. While such procedures such as Preimplantation Genetic Diagnosis (PGD) and sperm sorting are increasingly available in clinical settings, they raise profound ethical, legal, and religious concerns. This study critically explores the permissibility and implications of gender selection as an infertility treatment from the standpoint of Islamic jurisprudence (Sharīʿah). Drawing upon classical Islamic legal sources, contemporary fatwas, and the principles of maqāṣid al-sharīʿah (objectives of Islamic law), the paper investigates the legitimacy of gender selection under various intentions whether medical, social, or preferential. The analysis evaluates whether such practices align with the preservation of lineage (ḥifẓ al-nasab), protection of progeny (ḥifẓ al-nasl), and the ethical boundaries established in Islam. The paper further discusses the conditions under which gender selection may be deemed permissible or prohibited, offering a nuanced juristic framework to guide medical practitioners, ethicists, and Muslim couples considering such interventions. This research contributes to the growing discourse on the intersection of reproductive technologies and Islamic bioethics, emphasizing the need for culturally and religiously sensitive policy formulations in Muslim societies.